Regulation of Innate Immune Responses by Autophagy: A Goldmine for Viruses - Pradel, Baptiste; Robert-Hebmann, Véronique; Espert, Lucile (Frontiers in Immunology, 2020)
Autophagy is a lysosomal degradation pathway for intracellular components and is highly conserved across eukaryotes. This process is a key player in innate immunity and its activation has anti-microbial effects by directly targeting pathogens and also by regulating innate immune responses. Autophagy dysfunction is often associated with inflammatory diseases. Many studies have shown that it can also play a role in the control of innate immunity by preventing exacerbated inflammation and its harmful effects towards the host. The arms race between hosts and pathogens has led some viruses to evolve strategies that enable them to benefit from autophagy, either by directly hijacking the autophagy pathway for their life cycle, or by using its regulatory functions in innate immunity. The control of viral replication and spread involves the production of anti-viral cytokines. Controlling the signals that lead to production of these cytokines is a perfect way for viruses to escape from innate immune responses and establish successful infection. Published reports related to this last viral strategy have extensively grown in recent years. In this review we describe several links between autophagy and regulation of innate immune responses and we provide an overview of how viruses exploit these links for their own benefit.